Efficacy Of Leptin And Adiponectin And Their Ratio As Prognostic Factor For IncreasedInsulin Resistance In Childhood Obesity : Adipokines study in child obesity - Haddawi, Karrar Haider; Al-Ziaydi, Ahmed Ghdhban; Al-Khalidi, Fatima Abd Al-Kathem (Medical Science Journal for Advance Research, 2023)
Background: Obesity is a chronic medical condition that is associated with a range of illnesses. Recently, there has been a suggestion that the leptin -to -adiponectin ratio (L/A) could serve as a novel indicator for predicting metabolic disorders and various other chronic illnesses. This study aimed to examine the predictive capacity of leptin and adiponectin hormones, specifically focusing on their ratio, in identifying insulin resistance among obese children. The primary objective of this study is to assess the efficacy of the leptin-to-adiponectin ratio as an early prognostic indicator. Materials and methods: This are a case-control study involving 100 children/adolescents aged 8–16 years old. Anthropometric and biochemical measures were examined, applying World Health Organization (WHO) growth standards to categorize weight status. Blood samples were collected to evaluate glucose, insulin, leptin, and adiponectin levels. Insulin resistance (IR) (homeostasis model assessment of insulin resistance (HOMA-IR) was computed from fasting serum insulin and glucose. Results: Adiponectin, leptin, and the L/A ratio accurately predicted IR among adolescents. Leptin is a significant predictor of HOMA -IR, with a coefficient (β) of 0.273, a 95% confidence interval (CI) of 0.118 to 0.428, and a p-value of 0.0007. The L/A ratio is also a significant predictor, with a coefficient (β) of 0.052, a 95% CI of 0.036 to 0.067, and a p-value of less than 0.0001. The R-squared value of the model is 0.56, indicating that 56% of the variance in HOMA -IR, can be explained by this model. Conclusions: This study provides evidence for the efficacy of leptin and the L/A ratio as potential indicators of prognosis for heightened IR in children with obesity. The findings of this research could have significant implications for the prognosis and treatment of IR in this particular childhood population.